1999
DOI: 10.1111/j.1745-4603.1999.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear Properties and Warner‐bratzler Tenderness Measurement of Beef 1

Abstract: The shear properties of raw and cooked beef and their relationship with Warner‐Bratzler (WB) tenderness measurement were evaluated. Shear tests were performed on four muscles, biceps femoris (BF), longissimus dorsi (LD), semimembranosus (SM), and semitendinosus (ST), with three different aging treatments (0, 1, and 2 weeks), using a specially designed device and the WB shear device. Raw beef exhibited a nonlinear behavior characterized by linearity at small deformations, stress yield at intermediate deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Our study found the decrease of 40.79% of WBSF after 4 weeks of aging. Lu et al (1999) proved that aging for 2 weeks had a significant effect on WBSF in beef. The shear force decreased from 70.93 N after slaughter to 62.18 N in beef aged for 2 weeks.…”
Section: Warner-bratzler Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found the decrease of 40.79% of WBSF after 4 weeks of aging. Lu et al (1999) proved that aging for 2 weeks had a significant effect on WBSF in beef. The shear force decreased from 70.93 N after slaughter to 62.18 N in beef aged for 2 weeks.…”
Section: Warner-bratzler Testmentioning
confidence: 99%
“…Many authors conducted studies on beef tenderness (Koohmaraie 1994;Lu et al 1999;Oliete et al 2005;Lepetit 2008;Brewer et al 2008) indicating many variables that affect meat properties, including post-mortem aging. Meat aging is a process involving post-mortem proteolysis of myofibrillar proteins in muscles.…”
mentioning
confidence: 99%